2008
DOI: 10.1016/j.neuron.2008.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Neural Circuitry Underlying the Regulation of Conditioned Fear and Its Relation to Extinction

Abstract: SUMMARY Recent efforts to translate basic research to the treatment of clinical disorders have led to a growing interest in exploring mechanisms for diminishing fear. This research has emphasized two approaches: extinction of conditioned fear, examined across species; and cognitive emotion regulation, unique to humans. Here, we sought to examine the similarities and differences in the neural mechanisms underlying these two paradigms for diminishing fear. Using an emotion regulation strategy, we examine the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

42
477
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 614 publications
(526 citation statements)
references
References 47 publications
42
477
2
5
Order By: Relevance
“…This protocol was designed to deliver current to the vmPFC and avoid cathodal effects on the prefrontal cortex. However, other brain regions involved in fear processing (i.e., the dorsolateral prefrontal cortex, Mungee et al., 2014; Asthana et al., 2013; Delgado, Nearing, LeDoux, & Phelps, 2008; and anterior cingulate cortex, Etkin, Egner, & Kalisch, 2011; Milad et al., 2007) may have been inadvertently stimulated. Also, tDCS was applied once for a duration of 10 min total and effects of tDCS may be expected to increase with greater duration and number of sessions (Brunoni et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This protocol was designed to deliver current to the vmPFC and avoid cathodal effects on the prefrontal cortex. However, other brain regions involved in fear processing (i.e., the dorsolateral prefrontal cortex, Mungee et al., 2014; Asthana et al., 2013; Delgado, Nearing, LeDoux, & Phelps, 2008; and anterior cingulate cortex, Etkin, Egner, & Kalisch, 2011; Milad et al., 2007) may have been inadvertently stimulated. Also, tDCS was applied once for a duration of 10 min total and effects of tDCS may be expected to increase with greater duration and number of sessions (Brunoni et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…First, the threat of shock manipulation may be qualitatively different from the emotional image manipulation used in the current study. Although the threat of a painful shock is associated with excitation in emotion-related areas of the human brain that include amygdala (Delgado, Nearing, Ledoux, & Phelps, 2008), it also activates pain-related areas including thalamus, insula, somatosensory cortex, and anterior cingulate cortex (Bingel & Tracey, 2008;Oshiro, Quevedo, McHaffie, Kraft, & Coghill, 2009;Starr et al, 2009), Although a reciprocal relation has been demonstrated between emotion and motor systems as well as pain and motor systems (Del Santo, Gelli, Spidalieri, & Rossi. 2007;Hoeger Bement, Dicapo, Rasiarmos, & Hunter, 2008), it is plausible that the neural mechanism underlying these interactions may be different.…”
Section: Discussionmentioning
confidence: 99%
“…We expected regions classically involved in reward processing to be modulated by the different conditions in the two tasks, in particular striatum and amygdala (Delgado, 2007;Delgado, Nearing, LeDoux, & Phelps, 2008;Lieberman & Eisenberger, 2009). Additionally, we explored activation in the DMPFC, a region involved in impression formation and mentalizing (Frith & Frith, 1999;Mitchell et al, 2006).…”
Section: Discussionmentioning
confidence: 99%